Robustness of shape parameter for Erlang and Weibull bayesian acceptance sampling plans - Bibi, Bushra; Ali, Sajid; Shah, Ismail (Scientia Iranica. Transaction E, Industrial engineering, 2025)
This article assesses the robustness of shape parameter for Bayesian acceptance sampling plans assuming Erlang and Weibull distributions. In particular, the prior information on the parameter is combined assuming different loss functions to derive different sampling plans. The cost model for the group sampling plans is studied by satisfying the constraints of producer's and consumer's risks for the Weibull sampling. The single sampling plan is compared with the group sampling plan and the results suggest that the group sampling plan performs better than the single sampling in terms of cost. It is noticed that the shape parameters of Erlang and Weibull distributions are not robust as claimed in the literature.